From pragmatics to dialogue - Weigand, Edda; Kecskés, István (Dialogue studies (DS),, 2018)
"This volume aims at building bridges from pragmatics to dialogue and overcoming the gap between two 'circles' which have cut themselves off from each other in recent decades even if both addressed the same object, 'language use'. Pragmatics means the study of natural language use. There is however no clear answer as to what language use means. We are instead confronted with multiple and diverse models in an uncircumscribed field of language use. When trying to transform such a puzzle of pieces into a meaningful picture we are confronted with the complexity of language use which does not mean 'language' put to 'use' but represents the unity of a complex whole and calls for a total change in methodology towards a holistic theory. Human beings as dialogic individuals use language as dialogue which allows them to tackle the vicissitudes of their lives. Dialogue and its methodology of action and reaction can be traced back to human nature and provides the key to the unstructured field of pragmatics. The contributions to this volume share this common ground and address various perspectives in different types of action game"--